Supplementation of calcium-fatty acid to lactating cow to increase milk production and performance of dairy cow - Wina, Elizabeth; Widiawaty, Yeni; Tangendjaja, Budi; Susana, IWR (Indonesian Animal Sciences Society, 2014)
One of energy sources for feedingÂ dairy cow is fat or oil, however, inclusion of fat or fatty acid at high level (>5% in the diet) may cause negative effect on rumen fermentation. Fat or fatty acid, therefore should be protected from its degradation in the rumen. The aim of this experiment was to evaluate protected product of palm oil fatty acid (Calcium fatty acid) made in the institute as feed supplement given on top of the ration. The first experiment was in vitro experiment using rumen liquor. Feed without and with Calcium fatty acid (Ca-FA) was incubated in buffer-rumen liquor and pH, total gas, ammonia and in vitro digetibility were measured. The second experiment was feeding trial with two treatments using 12 FH dairy cow divided into 2 groups with diet containing supplemntation 300 g of Ca-FA and other group is control treatment without supplementation. The feed was total mixed ration, comprises of elephant grass, ground corn, soybean meal, wheat pollard and coconut meal with protein content 15.1% and Net Energy for Lactation 1.53 Mcal/kg.. Feed was given to cow one month before parturition until 120 days of lactation period. Milk production was recorded daily. Faeces collection was done at the end of the experiments for 1 week to calculate total tract digestibility. The result of the in vitro experiment showed that no negative effect on in vitro rumen fermentation except higher digestibility (DMD Ca-FA addition vs control were 58.52% vs 53.99%) occurred due to addition of Ca-FA. The addition of Ca-FA increased milk production (11.41 vs 10.74 litre/day), but no effect on intake, total tract digestibility and milk quality, higher body weight of cow than control cow showing the benefit of using Ca-FA in the diet of dairy cow. In conclusion supplementation of Ca-FA at 300 g would be beneficial to increase milk production without negative impact. Key Words: Calcium-Fatty Acid, Dairy Cow, Milk, Production, Quality